An assessment of the genetic diversity of Cedrela balansae C. DC. (Meliaceae) in Northwestern Argentina by means of combined use of SSR and AFLP molecular markers - Soldati, Maria Cristina; Fornes, Luis Fernando; Van Zonneveld, Maarten; Thomas, Evert; Zelener, Noga (2017)
Cedrela balansae C.DC. is a native tree species in Argentina, severely exploited for its timber features. We performed a molecular analysis to understand the genetic diversity and its distribution in eight remaining populations, which are distributed within the species' range in the Argentine Yungas Rainforest. We used two molecular markers: (i) seven SSRs, selected from forty-five SSRs developed for phylogenetically close species belonging to the Meliaceae family and (ii) 382 polymorphic AFLPs. The He was 0.643 and 0.222 for SSRs and AFLPs, respectively. The moderate levels of genetic diversity were related to the limited size of the species' distribution area, the latitudinal position of populations, the impacts of logging and the species' spatial distribution pattern. Genetic differentiation among populations was low for both markers (4.9% and 4.1% for SSRs and AFLPs, respectively). Four genetic clusters homogeneously distributed were distinguished. These observations may relate to the considerable historical gene flow measured (3.71 and 4.47 for SSRs and AFLPs, respectively). To safeguard the currently existing genetic base in the species, we identify four priority populations for conservation. To date only one of these is located in a protected area. Therefore, it is urgent to apply additional conservation measures for the remaining populations.